Children's Perception of Animacy: Social Attributions to Moving Figures. (May 2021) - Hofrichter, Ruth; Mueller, Megan E.; Rutherford, M. D.
Adults describe abstract shapes moving in a goal-directed manner using animate terms. This study tested which variables affect school-aged children's descriptions of moving geometrical shapes. Children aged 5 to 9 years were shown displays of interacting geometrical shapes and were asked to describe them. Across participants, instructions, number of moving figures, whether a figure caught another, and complexity of the scene were manipulated. Nine-year-olds used significantly more animate phrases than 5-year-olds. Furthermore, we found an Age by Condition interaction. Five-year-olds made significantly more animate statements in the animate condition, while 7-year-olds and 9-year-olds were less affected by instructions. Scene complexity increased children's use of animate phrases. Number of agents present on the screen and whether a catch occurred did not impact children's animate attributions. Our results support the hypothesis that children, like adults, are attuned to animacy cues and describe chasing agents in animate terms.